2021
DOI: 10.1007/s00784-021-04114-0
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and stress in oral lichen planus: a systematic review and meta-analysis

Abstract: Objectives We present this systematic review and meta-analyses to evaluate current evidence on the prevalence of depression, anxiety, and stress in patients with oral lichen planus and their magnitude of association. Material and methods We searched PubMed, Embase, Web of Science, Scopus, PsycInfo, and Google Scholar for studies published before January 2021. We evaluated the quality of studies using a specific method for systematic reviews addressing prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 42 publications
4
22
0
1
Order By: Relevance
“…This study is a secondary analysis of our previous study in which a prevalence of anxiety, 51%, depression, 48%, and sleep disturbance, 50.5%, were found in OLP patients compared with healthy controls. The prevalence of anxiety identified in this study was similar to that reported in a recent metanalysis of De Porras-Carrique (54.7%) while the prevalence of depression then found was lower (31.19%) [ 5 ]. The high prevalence of depression in our sample may be explained by virtue of an analysis of Italian data in a recent epidemiological study of the European Observatory on Health System and Policies (2019), in which a higher proportion of the Italian population aged over 65 presented symptoms of depression (41%) compared to the European population (29%) [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study is a secondary analysis of our previous study in which a prevalence of anxiety, 51%, depression, 48%, and sleep disturbance, 50.5%, were found in OLP patients compared with healthy controls. The prevalence of anxiety identified in this study was similar to that reported in a recent metanalysis of De Porras-Carrique (54.7%) while the prevalence of depression then found was lower (31.19%) [ 5 ]. The high prevalence of depression in our sample may be explained by virtue of an analysis of Italian data in a recent epidemiological study of the European Observatory on Health System and Policies (2019), in which a higher proportion of the Italian population aged over 65 presented symptoms of depression (41%) compared to the European population (29%) [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…The patients commonly reported a complex symptomatology characterized by pain/burning and additional oral symptoms, such as xerostomia, dysgeusia and globus, with nK-OLP patients reporting a higher level of pain compared with K-OLP patients [ 4 ]. A greater prevalence of anxiety, depression and stress has been reported in OLP patients compared with the general population, which may contribute not only to the onset but also to the exacerbation of the disease, impairing in turn the patient’s quality of life [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These diseases either exhibit a long disease course or relapse easily, and also seriously affects the patient’s quality of life. Therefore, the prevalence of depression, anxiety, and stress is high in patients with oral inflammatory diseases ( 4 , 5 ). Although the pathogenesis of these diseases is largely unknown, an increase in various pro-inflammatory cells and cytokines has been shown to be involved in the development and perpetuation of these diseases ( 6 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stress related factors that cause psychological anxiety and depression are closely related to oral diseases ( 6 ). Many oral diseases are accompanied by a high incidence of anxiety and depression ( 7 , 8 ), and the prevalence of depression in oral squamous cell carcinoma reportedly exceeds 65% ( 9 ). Meanwhile, current evidence suggests that bad mental attitudes are not conducive to the prognosis of oral disease ( 10 ), while inflammatory mediators were found to be increased locally in the tumors of stressed rats ( 11 ).…”
Section: Introductionmentioning
confidence: 99%